GIS-material for the archaeological project: A medieval charcoal production pit at Grebo Prästgård - House construction next to Grebo vicarage - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to planned construction of houses, the Swedish National Heritage Board's contract archaeology division, UV Öst, has performed a preliminary investigation of the site UV 4:1, Grebo parish, Åtvidaberg municipality. In connection with this, the site UV 4:2 has also been delimited. Several archaeological sites in the area were known from earlier surveys. Because of an expansion of the planned development area, another preliminary investigation was made in Melskog 1:1, where a settlement was discovered. A charcoal production pit, dated to 1290-1410 AD, was excavated within UV 4:1. This whole area has constituted an iron production site, but since the site to a high level is damaged by modern earthworks, no further excavation is suggested. At the edge of UV 4:2, an area with graves disturbed by ploughing, trenches were dug to delimit the site to the south and west. The site has not been excavated. The remains within Melskog 1:1 consist of leached features as well as distinct hearths and cultural layers. Among the finds are prehistoric pottery and worked quartz and flint. Due to the borders of the development area, the site could not be delimited to the south and east.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the preliminary investigation was to determine the type, character, age and extent of the archaeological sites UV 4:1 and Melskog 1:1. The results of the investigation were to form the basis of future decisions by the County Administrative Board, regarding the archaeological remnants, and serve as guidance for the developer's future planning. As for UV 4:2, the specific aim was to delimit the remains to the south and south-east.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Riksantikvarieämbetet UV Öst har under maj 2005 genomfört en arkeologisk förundersökning inom UV 4:1, Grebo socken, Åtvidabergs kommun. I samband med denna har också en avgränsning av UV 4:2 gjorts. Anledningen var planer på att bygga villor i området. Från en tidigare arkeologisk utredning var ett flertal fornlämningar i närområdet kända. Med anledning av att exploatören har utvidgat sitt planområde tillkom ett område som inte tidigare undersökts arkeologiskt. Det nytillkomna området, Melskog 1:1, visade sig innehålla ett boplatsområde. Inom UV 4:1 förundersöktes en kolningsgrop som daterades till 1290-1410 e Kr. Hela området har utgjort ett järnhantverksområde som dock bedöms så pass förstört av moderna ingrepp att ytterligare antikvarisk åtgärd inte föreslås. I utkanten av UV 4:2, ett område med överplöjda gravar, genomfördes sökschaktsgrävning för att avgränsa fornlämningen mot syd och väst. I övrigt kvarligger dock fornlämningen. Lämningarna inom Melskog 1:1 utgörs av såväl urlakade anläggningar, tydliga härdgropar som fyndförande lager. Bland fynden finns förhistorisk keramik samt bearbetad kvarts och flinta. Gränserna för exploateringsområdet gav ej möjlighet att begränsa fornlämningen mot söder och öster.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den arkeologiska förundersökningen var att fastställa fornlämningen UV 4:1 och Melskog 1:1 art och karaktär, ålder och utbredning. Resultaten skulle utgöra underlag för Länsstyrelsens vidare bedömningar i ärendet, samt fungera som underlag för beräkning av kostnader för eventuella vidare antikvariska åtgärder. Inom UV 4:2 var syftet att specifikt avgränsa fornlämningen mot syd och sydöst.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: En medeltida kolningsgrop vid Grebo Prästgård - Villabygge i anslutning till Grebo Prästgård
Keywords: High Medieval; högmedeltid; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi